Polymeric Nanocarriers for Enhanced Blood-Brain Barrier Permeation in Neurological Drug Delivery - Talele, Chitrali; Aundhia, Chintan; Talele, Dipali; Shah, Niyati; Kumari, Mamta; Sadhu, Piyushkumar (Micro and Nanosystems, 2025)
The blood-brain barrier (BBB) serves as a formidable obstacle to the treatment of neurological disorders by restricting the passage of therapeutic agents into the central nervous system (CNS). Polymeric nanocarriers have emerged as innovative tools to enhance drug delivery across the BBB, improving the bioavailability and efficacy of treatments for various neurological diseases. This review explores the challenges associated with BBB permeability and highlights recent advances in polymeric nanocarrier design. Key strategies such as surface modification, ligand conjugation, and stimuli-responsive carriers are discussed to optimize BBB penetration. Furthermore, this review examines the therapeutic potential of nanocarrier-based approaches for treating neurodegenerative disorders, brain tumors, and stroke. By leveraging nanotechnology, polymeric nanocarriers offer a promising avenue to overcome BBB-related drug delivery limitations and advance CNS therapeutics.
Keywords: neurological drug delivery